Identifikasi Cacat Sambungan Las SMAW Tipe Butt Joint Pada Material Baja SS400 Menggunakan Metode Liquid Penetrant Test Dan Ultrasonic Test - Al Faiq, M Rauf; Hastuti, Sri; Hadi, Nur; Mulyaningsih, Nani (Journal of Welding Technology, 2025)
SMAW welding is a type of electric arc welding, where the electrode is melted by the heat generated from the electric arc between the electrode tip and the workpiece. The working principle of SMAW welding is to use heat from an electric arc to melt the base metal and the tip of the electrode coated with flux, which also functions as a filler material in the metal joining process. The purpose of this study is to determine the effect of variations in current strength and electrode type on the type of weld defects in SS400 steel material welding joints. In this study, weld defects identified from liquid penetrant testing showed six types of defects, namely crack, porosity, incomplete fusion, slag inclusion, over spatter, and undercut, while ultrasonic testing found four types of defects, namely crack, incomplete penetration, incomplete fusion, and slag inclusion. Liquid penetrant and ultrasonic testing data show that the welding process using currents of 120 A and 110 A with E7016 electrodes has the most defects, meanwhile, at a current of 100 A with E7018 electrodes, it is a welding parameter with weld results that are protected from welding defects. Based on the test data, it can be concluded that variations in current and electrode type affect the number and type of weld defects that appear, which are influenced by the welding process, the amount of current, the diameter and type of electrode, electrical polarity and penetration rate. These parameters in SMAW welding determine the efficiency and quality of metal joining results.